2022
DOI: 10.3390/ma15134453
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcium Carbide Residue on Strength Development along with Mechanisms of Cement-Stabilized Dredged Sludge

Abstract: The purpose of this research is to explore the feasibility of using calcium carbide residue (CCR), a by-product from acetylene gas production, as a solid alkaline activator on the strength development in CCR–Portland cement-stabilized dredged sludge (CPDS). The effects of cement content, CCR content and curing time on the strength development of CPDS were investigated using a series of unconfined compressive strength (UCS), pH and electric conductivity (EC) tests. Scanning electron microscopy and X-ray diffrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 54 publications
0
0
0
Order By: Relevance
“…As shown in ref. [28], |G*| also gradually increases when reduced frequency increases. This indicates that low temperatures and high frequencies can bring about a significant increase in the resistance of SILT-CRMA, in the case of repeated shearing.…”
Section: Temperature Frequency Scanningmentioning
confidence: 96%
“…As shown in ref. [28], |G*| also gradually increases when reduced frequency increases. This indicates that low temperatures and high frequencies can bring about a significant increase in the resistance of SILT-CRMA, in the case of repeated shearing.…”
Section: Temperature Frequency Scanningmentioning
confidence: 96%
“…In recent studies, dredged material was treated with a blend of FA, PC, hydrated lime (HL) and fibers to produce compressed stabilized earth bricks (CSEBs) [20], while a report on the mixture of DM and recycled concrete concluded that mixtures containing 20% DM met the minimum road subgrade properties [21]. The stabilization mechanism and strengthening processes of these traditional stabilizers have been well-characterized in several studies [22][23][24][25], and the relationship between strength and water distribution was investigated using nuclear magnetic resonance spectroscopy [26]. Non-traditional stabilizers including ionic stabilizers, sulphonated limonene and enzyme emulsion are available in concentrated liquid forms, which are diluted with water prior to application and marketed as potential alternatives to traditional calcium-based stabilizers such as lime and cement [27,28].…”
Section: Introductionmentioning
confidence: 99%